Analisis Kinerja Portofolio Saham Perusahaan Pada Sektor Jasa Penerbangan Di Beberapa Negara Asean - Iftikar Arif Yuri; Nur Octasari Lisadi; Maya Rizki Sari (Institut Bisnis dan Informatika Kesatuan, 2021)
The Covid-19 pandemic that occurred in early 2020 in the world resulted in many businesses and companies being affected, handling companies in the aviation sector in ASEAN countries. As an investor who is going to invest, of course, you have to assess how the performance of the stock is, whether it will provide good and profitable returns, because the purpose of investors in investing in the capital market is of course to get a good increase (return). Portfolio performance evaluation is the final stage of the investment management process which aims to assess whether the portfolio that has been formed has a good performance and is in accordance with investment objectives. Among them are using the Sharpe, Treynor, and Jensen measurement models. The results showed that the Sharpe Method of Measurement found that the Garuda Indonesia company (-0.9144) had a greater risk and its performance was arguably the lowest compared to the other 3 companies because the Sharpe index value of Garuda Indonesia was higher risk than AirAsia Berhad-Malaysia (-0, 4823), Bangkok Airline-Thailand (-0.4703), and Nok Airlines Public Company-Thailand (-0.1133). None of the portfolios of these 4 companies produced better performance, in fact showed less performance than the benchmark. Meanwhile, the Treynor and Jensen methods also show that the performance of these companies underperforms against the benchmark.